The effect of the freestyle arm entry on exposure time to shoulder stress, the index of coordination, and swimming velocity - Havriluk, R. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Previous research examined the difference between sexes in freestyle technique and found that at the completion of the arm entry most females had the hand above the shoulder (AS) and most males had the hand level with the shoulder (LS), resulting in a longer exposure time to shoulder stress (ET) for females. Other research has shown that a higher index of coordination (IdC) in freestyle is related to a faster swimming velocity (SV). The purpose of the present study was to examine the effect of different arm entries (AS and LS) on ET, IdC, and SV. It was hypothesized that an LS arm entry would have a shorter ET and a positive impact on performance by increasing IdC and SV. University swimmers (70 male and 38 female) were tested with the standard Aquanex protocol. There was a significant difference between sexes with an LS used by 29% of the females and 54% of the males (p < .05). There were significant differences (p < .05) between sexes in ET, IdC, and SV. Males had a shorter ET, a higher IdC, and a faster SV. The LS group had a significantly shorter ET and higher IdC for both males and females (p < .05). The LS group had a faster SV for both males (p < .05) and females (ns). The results show that swimmers benefit from an LS arm entry with a shorter ET (to minimize the risk of shoulder injury) and a higher IdC that can increase SV.